The politics and economics of recovery in colonial Philippines in the aftermath of World War I, 1918-1923 - Ybiernas, Vicente Angel S. (Animo Repository, 2014)
Record Philippine trade with the United States during the World War I period led to increased public revenue collection, which in turn influenced the revision of the country's economic development program from a neoliberal to a state-led framework. After the end of war and the institution of "economic normalcy" in the United States, the state-led development framework in the Philippines came under serious scrutiny. Governor Leonard Wood's administrative priority as part of his "reform" agenda was to reverse the state-led development framework back to the previous neoliberal policy. The reversal was vehemently opposed by influential Filipino leaders in government for political and economic reasons. The conflict over development policy reached its climax in 1923 when all the Filipino members of Wood's cabinet resigned their positions in protest of the chief executive's perceived obstinacy. © 2014 by De La Salle University Publishing House.